Answer:
y = x³ + 2x² - 13x + 10
Step-by-step explanation:
Given
y = (x + 5)(x - 1)(x - 2) ← expand (x - 1)(x - 2)
= (x + 5)(x² - 2x - x + 2)
= (x + 5)(x² - 3x + 2)
Multiply each term in the second factor by each term in the first factor
= x(x² - 3x + 2) + 5(x² - 3x + 2) ← distribute both parenthesis
= x³ - 3x² + 2x + 5x² - 15x + 10 ← collect like terms
y = x³ + 2x² - 13x + 10
Answer:
a relationship or expression involving one or more variables
Answer:What’s your question?
Step-by-step explanation:
A)
x^2 - 6x + c = - 5 + c
using a^2 - 2ab + b^2 = (a-b)^2
so
6x = 2 * x * 3
so
c = 9
Answer
c = 9
b)
substitute c = 9
x^2 - 6x + 9 = - 5 + 9
(x - 3)^2 = 4
Answer:
(x - 3)^2 = 4
c) solve for x
(x - 3)^2 = 4
(x - 3)^2 = 2^2
so
x - 3 = 2
x = 5
and
x - 3 = -2
x = 1
Answer: x = 1 , 3